The Business Innovation in the Context of the Pandemic 2020 - 2021 - Giudice Baca, Victor (2021)
The Corona Virus Pandemic - 19 has tragically damaged World Tourism, Tourist Aviation, Cruise Travel, Hotel Businesses, Regional Transportation and Restaurants of the countries in general. The Ministry of Tourism of the Spanish State has disseminated 25 Innovations in Tourism and created the Strategy for Smart Tourist Destinations (DTI). ITDs have spread rapidly in countries with the greatest dependence on tourism such as Peru, Mexico and Argentina. In the period of the Pandemic, new Cross-Border Electronic Companies such as Dark Stores and Dark Kitchens have appeared. Supermarkets are moving to Electronic Commerce.